2002
DOI: 10.1007/bf02708009
|View full text |Cite
|
Sign up to set email alerts
|

Mössbauer studies on athermal martensite formation in an fe-ni-mn alloy

Abstract: In this study, austenite-martensite phase transformations which are formed by cooling effect in Fe-30% Ni-0⋅ ⋅2% Mn alloy are investigated with Mössbauer spectroscopy and scanning electron microscopy. The single peak of the paramagnetic phase and the six peaks of the ferromagnetic phase of Fe-30% Ni-0⋅ ⋅2% Mn alloy were observed in the Mössbauer spectrum. The internal magnetic field strength of ferromagnetic martensite phase was determined as 33⋅ ⋅8 T and the isomer shift values were determined as-0⋅ ⋅11 mm⋅ ⋅… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 6 publications
1
7
0
1
Order By: Relevance
“…On the other hand, Mo ¨ssbauer spectroscopy is known as one of the useful and most sensitive techniques to clear out the magnetic characters of the material and to estimate the volume fractions of austenite and martensite phases. [16][17][18][19] The Mo ¨ssbauer effect is a well known resonance absorption effect created by c rays owing to the change in the energy levels of atomic nuclei and also can determine isomer shift values and internal magnetic field of martensite. 4 Although it is well known that martensite volume fraction increases with increasing austenitising temperature and cooling rate, there has been no study reported about the effect of martensite amount on the magnetic properties of alloys.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Mo ¨ssbauer spectroscopy is known as one of the useful and most sensitive techniques to clear out the magnetic characters of the material and to estimate the volume fractions of austenite and martensite phases. [16][17][18][19] The Mo ¨ssbauer effect is a well known resonance absorption effect created by c rays owing to the change in the energy levels of atomic nuclei and also can determine isomer shift values and internal magnetic field of martensite. 4 Although it is well known that martensite volume fraction increases with increasing austenitising temperature and cooling rate, there has been no study reported about the effect of martensite amount on the magnetic properties of alloys.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study of authors [27], lath martensite morphology is observed in the austenite phase of 14 h homogenized Fe-30% Ni-0.2% Mn alloy after the current thermal affect. In the present study, thermally induced martensite showed a morphologic variety from partially twinned lenticular (denoted with symbol ␣ with a bcc crystal structure in Fig.…”
Section: Discussionmentioning
confidence: 92%
“…[10][11][12][13][14] From a morphological point of view, reported results for ferrous martensite compromises that a variety of morphologies, i.e. lath, butterfly, lenticular and thin plate 2,15-18 can be seen within thermally induced transformations for different alloy compositions.…”
Section: Introductionmentioning
confidence: 78%
“…14,[20][21][22] This case is also generalised by Shimizu and Kakeshita 1 as that many ferrous alloys and steels undergoing martensitic transformation are paramagnetic or ferromagnetic in the austenitic state, but they are all ferromagnetic in the martensitic state.…”
Section: Introductionmentioning
confidence: 95%